2007
DOI: 10.1149/1.2426800
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Low Resistance, and Flexible Amorphous ZnO-Doped In[sub 2]O[sub 3] Anode Grown on a PES Substrate

Abstract: Transparent and low resistance amorphous ZnO-doped In 2 O 3 ͑IZO͒ anode films were grown by radio-frequency ͑rf͒ sputtering on an organic passivated polyethersulfone ͑PES͒ substrate for use in flexible organic light-emitting diodes ͑OLEDs͒. Under optimized growth conditions, a sheet resistance of 15.2 ⍀/ᮀ, average transmittance above 89% in the green range, and a root mean square roughness of 0.375 nm were obtained, even for the IZO anode film grown in a pure Ar ambient without the addition of oxygen as a reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…GAXRS plot of single layer IZO film exhibited a broad peak at 2θ ¼32.7°, indicating a completely amorphous structure formed by Zn doping, as was previously reported. The amorphous structure of the IZO films can be explained by the immiscibility of ZnO and In 2 O 3 [34]. In the case of MIZO films, another broad peaks was observed at 2θ ¼27.59°due to the presence of amorphous MoO 3 on the surface region of the IZO film.…”
Section: Resultsmentioning
confidence: 95%
“…GAXRS plot of single layer IZO film exhibited a broad peak at 2θ ¼32.7°, indicating a completely amorphous structure formed by Zn doping, as was previously reported. The amorphous structure of the IZO films can be explained by the immiscibility of ZnO and In 2 O 3 [34]. In the case of MIZO films, another broad peaks was observed at 2θ ¼27.59°due to the presence of amorphous MoO 3 on the surface region of the IZO film.…”
Section: Resultsmentioning
confidence: 95%
“…The lower binding energy peak (O II ) is from the O 2À ions, which have neighboring indium atoms with their full complement, and the higher binding energy peak (O I ) corresponds to oxygen-deficient regions [25]. Because the increase of oxygen flow ratio leads to the incorporation of the oxygen atom into the ITO electrode, the flexible ITO electrode grown at the Ar/O 2 flow ratio of 30/3 shows lowest O II peak intensity, which is related to oxygen vacancies [26]. 10 shows the XRD plots obtained from the flexible ITO electrodes as a function of Ar/O 2 flow ratio.…”
Section: Article In Pressmentioning
confidence: 99%
“…However, some nanocrystallines, as indicated by arrows are embedded in the amorphous ITO matrix, due to the low amorphous/polycrystalline transformation temperature. Even if an ITO electrode is prepared at room temperature, nanocrystallines could be easily formed at the amorphous ITO matrix at a low homogeneous temperatures (T/T m o0.19-150 1C) [26,27]. It was shown that the flexible ITO layer is well defined on a PET substrate, indicating the absence of significant interfacial reactions between the ITO and the PET substrates due to the low substrate temperature.…”
Section: Article In Pressmentioning
confidence: 99%
“…Unlike the most popularly studied amorphous ITO (indium tin oxide) that is easily crystalized at a low temperature, amorphous IZO has a much higher crystallization temperature than ITO. Therefore, amorphous IZO is more favorable than amorphous ITO as a conducting film on a flexible substrate because there are no grains and grain boundaries in an amorphous film, and there is much less chance to generate internal stress and severe film cracking [2]. Although amorphous IZO has these great advantages, it also has a big drawback of low conductivity especially when amorphous IZO is deposited at a low processing temperature.…”
Section: Introductionmentioning
confidence: 99%